Científicos activistas, activismos epistémicos y gestión pública del ambiente en la gestión del sitio RAMSAR Delta del Paraná 2016-2020 (Papeles, 2021)
The aim of this work is to consider two concepts mobilized for the management of the RAMSAR Delta del Paraná site, determine their origins and who uses them in order to make visible the interaction ofknowledge that they bear witness to. We will present here two concepts: the first, ecocide, a concept mobilized from activism in the face of exceptional fires during 2020. The second concept is related to the state organization to govern a territory and to the new demands of this particular site for federalism. The methodology is qualitative, based on interviews with key agents, participant observation of CIM meetings and analysis of the documentation produced on the site.